AI-Supported Teacher Training for Ecological Thinking in STEM-Based Character Education: A Case Study of Early and Primary Islamic Schools in East Nusa Tenggara (Current Research in Education: Conference Series Journal, 2024)
This study aims to strengthen both teachers’ and students’ ecological awareness and moral sensitivity through Artificial Intelligence (AI)-supported professional development in Science, Technology, Engineering, and Mathematics (STEM) based character education. Using an action research approach, the program involved 130 teachers from early and primary Islamic schools in East Nusa Tenggara who were trained to design lesson plans and develop digital learning media integrating ecological thinking and sustainability values. Data were collected from lesson plan analyses, reflective journals, and teacher evaluations. Quantitative results indicate a 41% increase in teachers’ efficiency in lesson planning and a 63% improvement in creativity when applying AI tools. Qualitative findings revealed that classroom practices designed after the training promoted stronger environmental care, empathy, and social responsibility among students. Teachers noted that AI applications simplified idea generation and documentation processes, allowing more focus on student-centered learning and value integration. These findings suggest that AI serves not only as a technological support but also as a reflective partner in promoting character-oriented and environmentally responsible pedagogy. The study concludes that AI-assisted teacher training offers a practical model for implementing eco STEM learning that enhances sustainable character development and ecological literacy among students in Islamic education.